The Influence of Financial Literacy, Risk Tolerance and Trust on Cryptocurrency Investment Decision-Making on The Millennial Generation In Jabodetabek - Trisno, Andhika Muhammad Fadil; Fariyanti, Anna; Anggraeni, Lukytawati (Green Publisher Indonesia, 2025)
This study examines the influence of financial literacy, risk tolerance, and trust on cryptocurrency investment decision-making among the millennial generation in Jabodetabek. Cryptocurrency adoption in Indonesia has surged, with millennials as the dominant investor group, despite the inherent risks such as price volatility and regulatory uncertainty. Using the Theory of Planned Behavior (TPB) as the theoretical framework, this research investigates how attitudes, subjective norms, and perceived behavioral control, alongside financial literacy, risk tolerance, and trust, affect millennials’ decisions to invest in cryptocurrencies. A quantitative approach was employed, surveying 325 millennial investors across Jabodetabek. The findings indicate that attitudes, subjective norms, perceived behavioral control, risk tolerance, and trust significantly influence investment intentions and behavior. Contrarily, financial literacy showed no significant direct effect on investment intentions, suggesting that even investors with limited financial knowledge are inclined to invest due to positive attitudes and social influences. Risk tolerance and trust were found to play critical roles in shaping investment decisions, highlighting the importance of psychological factors in navigating cryptocurrency markets. These insights provide valuable implications for policymakers, financial educators, and cryptocurrency platform developers to foster more informed and responsible investment behaviors among young investors